Grass lignin: biosynthesis, biological roles, and industrial applications - Peracchi, Luigi M.; Panahabadi, Rahele; Barros-Rios, Jaime; Bartley, Laura E.; Sanguinet, Karen A. (Frontiers in Plant Science, 2024)
Lignin is a phenolic heteropolymer found in most terrestrial plants that contributes an essential role in plant growth, abiotic stress tolerance, and biotic stress resistance. Recent research in grass lignin biosynthesis has found differences compared to dicots such as Arabidopsis thaliana. For example, the prolific incorporation of hydroxycinnamic acids into grass secondary cell walls improve the structural integrity of vascular and structural elements via covalent crosslinking. Conversely, fundamental monolignol chemistry conserves the mechanisms of monolignol translocation and polymerization across the plant phylum. Emerging evidence suggests grass lignin compositions contribute to abiotic stress tolerance, and periods of biotic stress often alter cereal lignin compositions to hinder pathogenesis. This same recalcitrance also inhibits industrial valorization of plant biomass, making lignin alterations and reductions a prolific field of research. This review presents an update of grass lignin biosynthesis, translocation, and polymerization, highlights how lignified grass cell walls contribute to plant development and stress responses, and briefly addresses genetic engineering strategies that may benefit industrial applications.